Asthma and Tuberculosis: Implications for Onset, Clinical Progression, and Therapeutic Management - Christophe Malomalo Limanga; Nathanaël Mago Zokolea; Freddy Mombula Mondende (SAR Journal of Medicine, 2026)
Introduction: Asthma and tuberculosis (TB) are two major lung diseases whose coexistence could alter the risk of onset, clinical course, and therapeutic management of TB. This review aimed to synthesize the available data on the impact of asthma on these various aspects. Methods: A narrative literature review was conducted in PubMed, Semantic Scholar, Google Scholar, and the Cochrane Library. Publications in English or French published between 2010 and 2025 were considered. Original articles, systematic reviews, meta-analyses, and clinical guidelines addressing the asthma–tuberculosis relationship were included. Results: The data suggested that asthma may increase susceptibility to TB, primarily through the prolonged use of inhaled or systemic corticosteroids, with a dose-dependent effect. A Th1/Th2 immune imbalance, certain genetic factors, and common environmental and socioeconomic determinants may also play a role. The coexistence of the two diseases could lead to atypical clinical presentations and therapeutic challenges, particularly due to interactions between rifampin, corticosteroids, isoniazid, and theophylline. However, some data suggested a possible protective effect of eosinophilic inflammation. Conclusion: Asthma may promote the onset, reactivation, and progression of TB, but the evidence remains mixed and is primarily observational. Longitudinal and interventional studies are needed to clarify this association and optimize the management of patients with this comorbidity.